To find the equation that has the solution \( x = 3 \), let's substitute \( x = 3 \) into each option and see which one holds true.
-
Option 1: \( 3x + 8 = 41 \)
Substitute \( x = 3 \): \[ 3(3) + 8 = 9 + 8 = 17 \quad \text{(not equal to 41)} \]
-
Option 2: \( 4x - 2 = 10 \)
Substitute \( x = 3 \): \[ 4(3) - 2 = 12 - 2 = 10 \quad \text{(this is true)} \]
-
Option 3: \( 9x + 1 = -28 \)
Substitute \( x = 3 \): \[ 9(3) + 1 = 27 + 1 = 28 \quad \text{(not equal to -28)} \]
-
Option 4: \( 2x + 3 = 20 \)
Substitute \( x = 3 \): \[ 2(3) + 3 = 6 + 3 = 9 \quad \text{(not equal to 20)} \]
From the evaluations, only Option 2: \( 4x - 2 = 10 \) is true when \( x = 3 \).
Thus, the answer is: 4, x - 2 = 10.